Increased exfoliation of immature germ cells detected in semen analysis routine and its clinical significance - Fernando Tadeu Andrade-Rocha; Walter D. Cardona Maya (Archivio Italiano di Urologia e Andrologia, 2022)
To the Editor, Currently, semen analysis is the unique test to evaluate men’s fertility potential. Semen analysis provides valuable information on sperm production and quality. In addition to the conventional assessment of the sperm characteristics in a basic semen analysis routine, performing a differential diagnosis of leukocytes and sperm precursors immature germ cells (IGC) is also pivotal, due to adding valuable and clinically suitable information to the semen report [...].